Clinical Study to Investigate the Possibility of Using the Mandibular Occlusal Plane for Determining the Maxillary Occlusal Plane in Complete Dentures According to Patient’s Gender (Journal of Hama University, 2021)
Occlusal plane orientation is an important factor in the construction of a complete denture. Occlusal plane could be oriented using landmarks in the mandibular arch as well as in the maxillary arch. The aim of this study is to investigate the possibility of using the mandibular occlusal plane for determining the maxillary occlusal plane in complete dentures, and the effect of patient’s gender on it. The sample included 40 edentulous patients, ranging in age between 41-84 years (20 male and 20 female).The base plates had anterior wax rims that extend from the canine to the canine only in the maxillary and mandibular.On the master cast of the mandibular had been determined the posterior occlusal plane at both sides, in line with the convergence of the middle third with the upper third of the retromolar pad, and the posterior wax height of the mandibular was built according to this level. The posterior lower wax height was adjust to fit the lateral border of the tongue and the commissure of the lips. The posterior wax rims of maxillary was made according to the posterior wax rims of mandibular.The relationship of the posterior maxillary occlusal plane to Ala-Tragus line was examined using a double-level ruler specially designed for this purpose.The data obtained was statistically analyzed using Student’s independent T-test and Chi Square Test. The level of confidence was set at 95%.There was no statistically significant difference in the measured angle values between the maxillary occlusal plane that determined by the mandibular occlusal plane and Ala-Tragus line (P-value= 0.653), and there was no statistically significant difference in the reproducibility of maxillary occlusal plane situation compared with Ala-Tragus Line (P-value= 0.801), according to patient’s gender.The results showed the possibility of using the mandibular occlusal plane for determining the maxillary occlusal plane in complete dentures, and the patient’s gender had no effect on it.